2016
DOI: 10.1007/s11010-016-2830-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-arthritogenic and cardioprotective action of hesperidin and daidzein in collagen-induced rheumatoid arthritis

Abstract: Atherosclerosis has been linked to chronic inflammatory processes. Changes in the levels of lipoproteins, especially low-density lipoprotein or its variants, as well as inflammatory markers are risk factors for the atherosclerosis. In the present study, an experimental model of rheumatoid arthritis was developed by administrating collagen suspension intradermally in the tail region of Wistar albino rats. At the same time, a suspension of hesperidin (50 mg/kg body weight) and daidzein (20 mg/kg body weight) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…In addition, in male middle-aged rats with HFD used to induce atherosclerosis, treatment with daidzein (30 mg/kg body weight) decreased the serum cholesterol and increased TG level (Sosi c-Jurjevi c et al, 2007). In another study using rheumatoid arthritis rat model, it was shown that intragastric administration of daidzein (20 mg/kg body weight) and hesperidin (50 mg/kg body weight) reduced plasma VLDL, LDL-C, and TG concentrations, while increasing HDL-C levels (Ahmad et al, 2016).…”
Section: Namentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, in male middle-aged rats with HFD used to induce atherosclerosis, treatment with daidzein (30 mg/kg body weight) decreased the serum cholesterol and increased TG level (Sosi c-Jurjevi c et al, 2007). In another study using rheumatoid arthritis rat model, it was shown that intragastric administration of daidzein (20 mg/kg body weight) and hesperidin (50 mg/kg body weight) reduced plasma VLDL, LDL-C, and TG concentrations, while increasing HDL-C levels (Ahmad et al, 2016).…”
Section: Namentioning
confidence: 97%
“…Decreased the serum cholesterol, increased triglyceride (TG) level in the male middleaged rats with HFD (Sosi c-Jurjevi c et al, 2007), reduced plasma VLDL, LDL-C, and TG concentrations, while increased the HDL-C levels in a rheumatoid arthritis rat model (Ahmad et al, 2016). Daidzein was reported to be an inhibitor of HMG-CoA reductase, ACAT1, and ACAT2 (Borradaile et al, 2002;Sung et al, 2004).…”
Section: Daidzeinmentioning
confidence: 99%
“…Hence, appropriate intake of linoleic acid has effective anti-RA activities [14][15][16] . Daidzein and daidzin can ameliorate RA symptoms and decrease RA occurrence [17][18][19][20] . Our results demonstrated that the content of linoleic acid in TF11 was higher than that of TF32, while the daidzin content of TF32 was higher than either TF11 or TF23 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…DZ has been reported to have several health benefits . Studies have shown that DZ possesses antioxidant, anti‐inflammatory, antiapoptotic, anticancer, MAPK signaling pathway modulating, and neuroprotective properties. The nephroprotective effect of DZ in mice has recently been demonstrated using a 3‐day model of CIN.…”
Section: Introductionmentioning
confidence: 99%